Pengaruh Religiusitas dan Long Term Orientation terhadap Budgetary Slack di Organisasi Perangkat Daerah (OPD) Kota Padang - Zira Atika Putri; Sany Dwita (Universitas Negeri Padang, 2024)
Budgetary Slack is common in public sector organizations, due to a tight budget system that is difficult to realize. Factors that affect the budget gap are one of personal values. This study aims to look at individual factors of religiosity and long-term orientation. Research on religiosity factors in the context of budgets is still not widely carried out, especially regarding budgetary measures. This research method is descriptive quantitative with survey techniques using questionnaires. This research was conducted on the structural OPD of Padang City. Based on the results of testing and analysis, the religiosity variable has a positive effect on budgetary slack, and long-term orientation positively affects the occurrence of budget shortages in regional apparatus organizations. The findings of this study are expected to contribute research in management science and public sector accounting, especially related to budgets in the public sector.